Empirical Investigation of Abnormal Returns through Technical Analysis in the Nepalese Stock Market - Lama, Arun Krishna (The Journal of Economic Concerns, 2023)
This study comprehensively assesses the potential superiority of a technical trading strategy compared to the conventional buy and hold approach in the Nepalese stock market, where prior research is limited. It investigates the effectiveness of three widely recognized technical analysis indicators, both individually and in combination, using a 12-year historical dataset of 75 stocks, and 25.65-year NEPSE (Nepal Stock Exchange) index data. The back testing procedure evaluates the profitability and viability of the technical analysis strategy relative to buy and hold. The results show that, when factoring in trading-related costs, the technical trading strategy does not consistently outperform buy and hold. However, when trading fees are excluded, the technical strategy exhibits statistically significant outperformance. Future research can explore alternative technical rules and strategies to gain a more nuanced understanding of trading dynamics.